9 - Constructing Knowledge Societies? The World Bank and the New Lending Policy for Tertiary Education: Tor Halvorsen & Tom Skauge - Tor Halvorsen; Tom Skauge i (Journal of Higher Education in Africa, 2004)
Abstract